Assessment on the quality of compost produced by commercial producers and the potential for compost production in Kilinochchi district. - Pushparaj, M.; Gnanavelrajah, N. (Faculty of Agriculture, Eastern University, Sri Lanka., 2023)
Inorganic fertilizer supply has been limited in Sri Lanka since 2019, due to Covid 19 pandemic and the economic crisis. Therefore, farmers have to depend on organic fertilizers of which a viable alternative is compost. A quality compost could satisfy the nutrient requirements, and improve soil’s physical, chemical and biological properties. To ensure good crop response, it is important that the compost produced is of good quality, meeting the Sri Lankan standards (SLS). In this background, this study was focused to identify the knowledge and issues of commercial compost producers, assessing the quality of compost produced by commercial compost producers in the Kilinochchi district and to assess the potential compost production in Kilinochchi district. The knowledge and issues of commercial compost producers were evaluated through a questionnaire survey of 11 producers who were actively involved in production during the study period. The quality of the commercially produced compost samples was assessed through standard laboratory analysis. Potential compost production in Kilinochchi district was assessed through secondary data analysis. The results showed that 64% of producers practiced open space (unprotected) type of compost system. 64% of the producers participated in training programs regarding compost production. According to the survey, the main problems faced by producers are lack of initial investment for commercialization, less availability of inputs, and lack of knowledge on commercialization. Through compost quality analysis none of the samples complied all the physical and chemical parameters of SLS (1635:2019) requirement. The major issues identified in most of the samples of commercial producers were high sand content and low potassium content. Further, the results of secondary data analysis showed that the potential production of compost from locally available resources is more than enough to satisfy the crop requirement in the Kilinochchi district.
Keywords: Commercial compost producers; Kilinochchi district; Quality compost; Potential compost production